Awareness, Use and Users’ Satisfaction with Library E-Resources by Undergraduates of National Open University of Nigeria, Lagos Study Centre - Osimetha, Isah Seidu (West African Journal of Open and Flexible Learning, 2017)
The purpose of this study was to ascertain awareness, use and users’ satisfaction with library electronic resources by undergraduates of National Open University of Nigeria, Lagos Study Centre. In carrying out this study, four (4) research questions were posed. They are what is the level of undergraduate users’ awareness of library e-resources in NOUN? what is the level of undergraduate students’ use of library e-resources in NOUN? what is the level of undergraduate users’ satisfaction with library e-resources in NOUN? and what are the challenges faced by undergraduate students’ in the use of library eresources in NOUN? The study adopted survey design. Multistage sampling technique was used since the population was large. The study sample population comprised of 722 undergraduates of National Open University of Nigeria (NOUN), Lagos study Centre. The instrument used for data collection was a structured questionnaire. The research questions were answered using SPSS to determine frequencies, percentages, cross tabulations. The 2 hypotheses of this research were measured using linear regression analysis and multiple regression analysis. The major findings of the study revealed: lack of awareness of library e-resources, inaccessibility to some electronic resources, incessant power supply, poor internet access, inadequate computer facilities to access information. Based on these findings, the following recommendations were made: Library management should make sure students are given adequate orientation to increase their awareness and use of the library electronic resources. For users’ to be satisfied, there is need for appreciable level of power supply, improved infrastructure, improved Internet facilities among others.Résumé : Le but de cette étude était de vérifier la connaissance, l'utilisation et la satisfaction des utilisateurs des ressources électroniques de la bibliothèque par les étudiants de premier cycle de l'Université nationale ouverte du Nigeria, Lagos Study Centre. Dans le cadre de cette étude, quatre (4) questions de recherche ont été posées : Quel est le niveau de sensibilisation des étudiants de premier cycle aux ressources électroniques des bibliothèques dans NOUN ? Quel est le niveau d'utilisation des ressources électroniques des bibliothèques dans NOUN ? Quel est le niveau de satisfaction des étudiants de premier cycle à l'égard des ressources électroniques des bibliothèques dans NOUN ? Et quels sont les défis rencontrés par les étudiants de premier cycle dans l'utilisation des ressources électroniques des bibliothèques dans NOUN ? L'étude a adopté un plan d'enquête. La technique d'échantillonnage en plusieurs étapes a été utilisée puisque la population était importante. L'échantillon de l'étude comprenait 722 étudiants de premier cycle de l’Université Nationale de l’enseignement a distance du Nigeria (NOUN), Lagos study Centre. L'instrument utilisé pour la collecte des données était un questionnaire structuré. On a répondu aux questions de recherche en utilisant SPSS pour déterminer les fréquences, les pourcentages et les tableaux croisés. Les deux hypothèses de cette recherche ont été mesurées à l'aide d'une analyse de régression linéaire et d'une analyse de régression multiple. Les principales conclusions de l'étude ont révélé : méconnaissance des ressources électroniques des bibliothèques, inaccessibilité de certaines ressources électroniques, alimentation électrique incessante, mauvais accès à Internet, installations informatiques inadéquates pour accéder à l'information. Sur la base de ces constatations, les recommandations suivantes ont été formulées : La direction de la bibliothèque devrait s'assurer que les élèves reçoivent une orientation adéquate pour mieux connaître et utiliser les ressources électroniques de la bibliothèque. Pour que les utilisateurs soient satisfaits, il faut, entre autres, un niveau appréciable d'approvisionnement en électricité, une infrastructure améliorée et des installations Internet améliorées.
Keywords: Academic Libraries; e-resources; Awareness of library eresources; Use of Library e-resources; Users’ satisfaction with library e-resources